A General Linear Model Approach: Development Of Psychological Well-Being, Remote Working, Employee Engagement, Job Satisfaction, Scales, Data Analysis And Reporting Concerning To Information Technology Sector - Prasad, Dr. KDV; Mangipudi, Dr. Mruthyanjaya Rao (The journal of contemporary issues in business and government, 2021)
In this article the author elaborates on the construction and development of Remote Working, Employee Engagement, Job Satisfaction, Psychological well-being Scales, and the appropriated statistical methods needed to analyze the respondent’s data, reporting the results, using secondary data, with psychological well-being as a dependent variable. The measurement scales constructed are remote working 18 items, with 4 sub-scales; job engagement 20 items with 5 sub-subscales, work-life balance 18 items are the independent factors, which have a causal effect on a dependent factor psychological well-being of an employee which has 8 items with 6 sub-scales. The reliability of the survey instrument assessed measuring reliability statistic Cronbach alpha, construct validity, and content validity are tested using face validity and convergent validity taking expert opinion and factor analysis respectively. As the study is measuring six dependent variables related to the psychological well-being of an employee, the author has used the statistical procedure generalized linear model a multivariate multiple regression model, which allows more than one dependent variable in the system and the results were inferences and presented. The measured Cronbach’s alpha value indicates that the overall survey instrument was reliable and maintained internal consistency. The results of GLM indicate statistically gender and age differences that are influencing the psychological well-being of an employee. A notable observation was Self-Acceptance was statistically significant and influenced by almost all the predictor variables. The results were presented in detail and inferences provided wherever appropriate